Keterkaitan Keterampilan Argumentasi Ilmiah dan Berpikir Kritis Melalui Model Pembelajaran VAK pada Materi Sel - Maya Kharisma; Milla Listiawati; Iwan Ridwan Yusuf (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Scientific argumentation skills are high-level thinking skills that are very important for students to have in the learning process, especially in 21st century education that shapes students to argue and shape students into individuals who are able to think critically. However, based on the results of observations, students are still not active in conveying their arguments and critical thinking. The purpose of this study is to analyze the relationship between scientific argumentation skills and critical thinking skills through the VAK (Visual, Auditory, Kinesthetic) learning model on cell material. The method used in this study is the correlational method with an ex post facto research design using 1 experimental class with a research sample of 30 students. The instruments used are 15 essay questions for both scientific argumentation skills and critical thinking skills. Data analysis was carried out using Microsoft Excel and data analysis techniques using the t-test. The results of the analysis through the posttest on students' scientific argumentation skills are in the form of an average value of 47.5, while the average value of critical thinking skills is 47.6, with the results of the t-test being 2.08> 1.69, which means that tcount> ttable, namely H0 is rejected. The results of the hypothesis test show a significant relationship between scientific argumentation skills and critical thinking skills using the VAK (Visual, Auditory, Kinesthetic) learning model on cell material.